Doctor hopping and doctor shopping for prescription opioids associated with increased odds of high‐risk use. Issue 8 (5th June 2019) - Young, Sean G.; Hayes, Corey J.; Aram, Jonathan; Tait, Mark A.
Abstract: Purpose: Early detection of risky behaviors involving prescription opioids can assist prescribers in implementing safer prescribing. Patient‐to‐prescriber travel patterns may indicate potential opioid misuse. We introduce doctor hopping, patients bypassing nearby prescribers in favor of more distant ones, as a new spatial estimation of potentially risky behavior, and compare with traditional doctor shopping metrics. Methods: We examined all filled opioid prescriptions between 2015 and 2016 from the Arkansas Prescription Drug Monitoring Program. We calculated patient‐to‐prescriber travel times and number of prescribers bypassed for each prescription, adjusted for payment method. Opioid recipients traveling further than the nearest urban area and bypassing more prescribers than 99% of other recipients from the same zip code were identified as doctor hoppers. We calculated odds ratios to evaluate how doctor hopping and doctor shopping correspond to high‐risk opioid uses. Results: Approximately 0.72% of all opioid recipients in Arkansas engaged in doctor hopping two or more times during the study period. Rates of doctor hopping varied spatially but were more common in rural areas. Doctor shopping was more common in urban areas. Both hopping and shopping were significantly associated with higher odds of engaging in high‐risk opioid use. The combination of doctor hopping and doctor shopping metrics can predict high‐risk use better than either metric alone and may allow for earlier detection than doctor shopping alone. Conclusions: Doctor hopping is positively associated with high‐risk opioid use and is distinct from and complementary to doctor shopping. We recommend Prescription Drug Monitoring Program (PDMP) vendors incorporate similar spatial analyses into their systems.